DARIO ARGENTO ET LA MÈRE-SORCIÈRE : PSYCHANALYSE D’UNE IMAGE OBSÉDANTE - POP-CURȘEU, Ioan (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
Dario Argento and the Mother-Witch: Psychoanalysis of an Obsessive Image. This paper tries to present the complexity of the maternal figures in the work and biography of film director Dario Argento. The methods of interpretation are inspired by psychoanalysis, because Argento often referred to Freud’s writings in his films or in his recent autobiography, Fear, published in 2014. The criminal mothers depicted in some films signed by Dario Argento show, through violent narratives, the difficulties he had in dealing with the maternal imago. But the most striking embodiments of the maternal monstrosity are to be found in the figure of the mother-witch, in the trilogy composed by Suspiria (1977), Inferno (1980), La Terza Madre (2007). The mother-witch has, of course, biographical sources, but its presence in some classical fairy-tales or in fin-de-siècle decadent literature also inspired the film director.